The significance of cultural heritage law in Nigeria’s legal education and its relevance to other fields of law (2015)
Besides the fact that Africa is considered to be the cradle of civilization, it is widely acknowledged to be rich in culture. In fact, what Africa lacks in science and technology is compensated for in her rich cultural past, a heritage that is increasingly being assailed and plummeted by contemporary popular cultures especially from the western world. Whereas academics and culture experts have devoted considerable attention to the study of different aspects of African culture, legal academics apparently due to their adherence to traditional law subjects and perhaps limited training and exposure have hitherto abandoned discourse on cultural issues beyond the narrow confines of customary law to scholars and culture experts from among archaeologists, anthropologists, sociologists, ethnographers etc. This regrettable trend is being reversed with the introduction of Cultural heritage law, a relatively new field of law in Nigeria, at the Master’s level in the University of Ibadan. Though the course is relatively new, successive LL.M students are finding it attractive. The aims of this paper are two. First is to highlight the significance of Cultural heritage law in the law curriculum in view of the peculiar position of Nigeria in the cultural heritage map of the world. Secondly, this work will attempt to reveal the interface between cultural heritage law and other areas of law. The main goal is to demystify cultural heritage law and project beyond the successful experiment at the University of Ibadan by exploring how more students of law especially at the LL.B level can be introduced to the interesting union between law and material and ethereal culture.